2011
DOI: 10.1371/journal.pone.0027334
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behaviors and Reasons for not Getting Tested for HIV among Men Who Have Sex with Men: An Online Survey in Peru

Abstract: BackgroundMen who have sex with men (MSM) account for the greatest burden of the HIV epidemic in Peru. Given that MSM are frequent users of the Internet, understanding the risk behaviors and the reasons for not getting tested among MSM who surf the Internet may improve the tailoring of future online behavioral interventions.MethodsFrom October 2007 to April 2008, we conducted an online survey among users of seven Peruvian gay websites.ResultsWe received 1,481 surveys, 1,301 of which were included in the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 12 publications
(23 reference statements)
5
48
0
3
Order By: Relevance
“…En el análisis se encontró que los pacientes de sexo masculino y que los grupos sobre de 40 años de edad tienen mayor frecuencia de DT; estos datos se ven respaldados por hallazgos en estudios que indican que tanto la edad como el sexo se asocian a un DT de infección por VIH 31,32 . Smith y cols., encontraron una mayor frecuencia de DT y mortalidad en población adulta mayor con infección por VIH 32 , pudiéndose explicar por ciertos factores sociales y de hábitos de riesgo; también la inmunosenescencia propia del envejecimiento, reduce su potencial para recuperarse de la infección por VIH [31][32][33] . Además, la orientación sexual HSH y bisexual tuvieron más frecuencia de DT.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En el análisis se encontró que los pacientes de sexo masculino y que los grupos sobre de 40 años de edad tienen mayor frecuencia de DT; estos datos se ven respaldados por hallazgos en estudios que indican que tanto la edad como el sexo se asocian a un DT de infección por VIH 31,32 . Smith y cols., encontraron una mayor frecuencia de DT y mortalidad en población adulta mayor con infección por VIH 32 , pudiéndose explicar por ciertos factores sociales y de hábitos de riesgo; también la inmunosenescencia propia del envejecimiento, reduce su potencial para recuperarse de la infección por VIH [31][32][33] . Además, la orientación sexual HSH y bisexual tuvieron más frecuencia de DT.…”
Section: Discussionunclassified
“…Además, la orientación sexual HSH y bisexual tuvieron más frecuencia de DT. Blas y cols., identificaron en población peruana de HSH que "el miedo de tener un resultado positivo y el desconocimiento de lugares donde realizarse la prueba de VIH" son las razones más comunes para no realizarse la prueba de ELISA para VIH 33 , otras razones reconocidas son el estigma de tener infección por VIH, el nivel de conocimiento y/o la amenaza contra la identidad personal 29 . Los usuarios de drogas también tuvieron mayor DT; esto guarda relación con algunos estudios que demuestran que los usuarios de drogas ilícitas tienen mayor probabilidad de tener DT e inclusive EA [35][36][37] .…”
Section: Discussionunclassified
“…AUDs have previously been associated with decreased ART adherence in other settings and populations [55,56] and to other poor HIV-treatment outcomes, including decreased health care utilization [57], decreased linkage to and retention in care [58,59], reduced ART medication access [60,61] and viral non-suppression [58]. In Peru's largest biobehavioral serosurveillance study of over 5000 Peruvian MSM, AUDs were previously found to be highly prevalent (62.3%) and independently associated with high-risk sexual behaviors [26-28] and being unaware of being HIV-infected [29]. This study builds on these concerning findings and is the first to demonstrate a concerning association between AUDs and suboptimal ART adherence among HIV-infected MSM enrolled in HIV clinical care in Peru.…”
Section: Discussionmentioning
confidence: 99%
“…MSM represent a particularly vulnerable population in Peru, a middle-income country where the government provides free ART. Given the high levels of stigma against same-sex relations in Peru [23], the consumption of disinhibiting substances like alcohol is common among MSM [24,25], and is associated with high-risk sexual behaviors [26-28] and being unaware of being HIV-infected [29]. In light of these concerning findings, we hypothesized that mind-altering substances like alcohol and/or drugs or underlying NCI may also negatively impact HIV treatment outcomes, even in the presence of medication reminders.…”
Section: Introductionmentioning
confidence: 99%
“…Además, un reciente estudio Latinoamericano, donde participaron tres instituciones peruanas, constató una adecuada disponibilidad de recursos especializados para la atención del VIH 16 . Sin embargo, existen aún barreras principalmente sociales para diagnosticar y/o testear oportunamente el VIH, como son la falta de percepción de riesgo y el estigma de la infección VIH/SIDA en la población en general, por lo que no se realizan la prueba voluntariamente cuando debieran hacerlo [17][18][19][20] . Se recomienda que se realicen investigaciones que indaguen los factores que se asocian a que dichas barreras sociales sean un impedimento para un oportuno diagnóstico, sobre todo en la población que tiene más riesgo.…”
Section: Discussionunclassified